An expanded role for animal privacy and relational ethics in wildlife digital technology research - Kaehrle, Martin; Rubel, Alan; Streiffer, Robert (Frontiers in Conservation Science, 2025)
There is a growing body of research exploring the effects of digital technology (DT) on wildlife. In this perspective, we map a line of inquiry that links a growing body of work describing the effects of DT on wildlife, recent work on animal privacy, and contemporary work in animal normative moral theory (specifically relational ethics). We have three aims. Our first is to articulate conceptual and moral issues concerning animal privacy and relationality, issues often neglected or left implicit in existing guidance on using DT to manage wildlife information sharing. Our second is to identify areas needing further research. Our third is to urge researchers and practitioners involved in wildlife DT to explicitly address these issues so as to better advance our understanding of human ethical obligations to animals, species, ecosystems, and other humans in the context of DT.